MOTIVASI WISATAWAN BERKUNJUNG KE GEOPARK SILOKEK KABUPATEN SIJUNJUNG - Lingga Arend Sukma; Pasaribu; Rian Surenda (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2022)
This study aims to determine the motivation of tourists visiting the Silokek Geopark area in terms of 4 indicators, namely, novelty seeking, stress busting/fun, achievement, family oriented/education. This research is quantitative descriptive. The population of this study were domestic visitors who traveled to the Silokek Geopark, Sijunjung Regency, with a total sample of 100 respondents who had visited the Silokek Geopark. Collecting research data using a questionnaire with a Likert scale that has been tested for validity and reliability. Furthermore, the data were analyzed through descriptive analysis by looking at the total respondent's achievement (TCR). The results of this study indicate that the motivation of tourists visiting the Silokek Geopark, Sijunjung Regency is in the good category with an average value of 65.89. Based on the statistical results of the tourist motivation variable of 59% in the range of 56.66 < 67.99 with the agree category. Meanwhile for each indicator where novelty seeking 77.04% of respondents said it was quite good, 75.5% of respondents said Stress Busting/Fun was good enough, 75.55% of respondents said it was quite good, 77.7% family oriented/educational respondents said quite well.